Prediction of compost physicochemical properties using image-based feature extraction and machine learning - Anshuman Nayak; Lewis S. Rowles; Thomas Echols; Blake Bakaric; Carson Rowland; Connor Kinard; Tyler Barnett; Siddhant Sarang Kodolkar; Sarthak Jhanwar; Rishabh Moonka; Somsubhra Chakraborty; David C. Weindorf (Waste Management, 2026)

High‐Throughput Sequencing in Aquaculture Disease Investigations: Challenges and Opportunities for Implementation - Francisca Samsing; Phoebe Arbon; Matthew Arnold; Andrew C. Barnes; David Bass; Joy A. Becker; Jerusha Bennett; Charles Caraguel; Jeremy Carson; Vincenzo A. Costa; Thomas Dumond; Jemma Geoghegan; et al. (Reviews in Aquaculture, 2026)
The current generation of sequencing technologies can produce terabases of data with exceptional accuracy and speed, at a fraction of the cost of older methods. Despite this unprecedented power, adoption into aquaculture health management presents several challenges, including identifying where such capability may be optimally deployed. Here we synthesise discussions from a structured expert workshop held at the 2025 Aotearoa Aquatic Diseases Symposium in Dunedin, New Zealand, where experts from industry, government and academia explored the challenges and opportunities for adopting high‐throughput sequencing (HTS) to support disease investigations in aquaculture. Workshop participants identified key applications for HTS, including pathogen discovery during unexplained mortality events and source attribution in epidemics, but also noted technical, regulatory and social challenges for widespread adoption. These include the need for standardised sampling and bioinformatic workflows, data sovereignty, equitable access to the technology and uncertainty around interpreting detection of notifiable pathogens. Targeted research and coordinated regulatory frameworks will be essential to guide responsible use of HTS and determine where it adds value relative to existing approaches. Clarifying these opportunities and constraints will guide the responsible adoption of HTS into aquaculture health management to support sustainable growth for the sector.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A revised Proterozoic tectono-stratigraphy of the South Nicholson region, Northern Territory, Australia—insights from SHRIMP U–Pb detrital zircon geochronology - C. J. Carson; N. Kositcin; J. R. Anderson; P. A. Henson (Australian Journal of Earth Sciences, 2026)

Shale brittleness within the Paleoproterozoic Isa Superbasin succession in the South Nicholson region, Northern Australia - A. H. E. Bailey; A. J. M. Jarrett; L. Wang; B. L. Reno; E. Tenthorey; C. Carson; P. Henson (Australian Journal of Earth Sciences, 2026)

A Modern Ghost Story: Increased Selective Mortality of Salmon Under Climate Extremes - Anna M. Sturrock; Kirsten Sellheim; Joseph Merz; Jamie Sweeney; Miranda Bell‐Tilcock; George Whitman; Kohma Arai; Malte Willmes; Carson Jeffres; Rachel C. Johnson (Global Change Biology, 2026)
Hydroclimate volatility poses a growing threat to species' persistence, particularly when combined with widespread habitat loss and other stressors. Although the negative impacts of drought on aquatic species are well documented, wet conditions are generally assumed to enhance recruitment of migratory species during freshwater life stages. Life‐history theory predicts that species with multiple migratory strategies should be more resilient to climate extremes by spreading risk across time and space. Testing these assumptions requires tracking both survivors and ‘ghosts’ across life stages and broad spatial scales. For many Pacific salmonids, a substantial fraction of the population disperses downstream soon after emergence (‘early migrants’), rearing in downstream habitats before entering the ocean. The extent to which hydroclimatic conditions influence selection against this phenotype and its lifetime success is poorly understood. To address this data gap, we tracked nine cohorts of Chinook salmon ( Oncorhynchus tshawytscha ) at sequential points through their life cycle, using otolith and eye lens isotopes to identify habitats and conditions associated with the highest losses of early migrants. Comparisons of juvenile ( n = 2197) and adult ( n = 3937) samples revealed large spatiotemporal variation in the strength of selective mortality. Early migrants became progressively rarer at each consecutive sampling point, including among adult returns, indicating carryover effects from freshwater into the ocean. At the southern edge of the species range—where water scarcity is an intensifying issue—we had predicted positive relationships between river flow, growth and survival. Instead, trends were consistently quadratic, suggesting that both drought and extreme high flows can reduce rearing opportunities and cohort strength. Ultimately, all phenotypes contributed to reproduction in all years, underscoring the importance of maintaining diverse life history portfolios and implementing climate‐ready restoration strategies that provide refugia and growth opportunities across the full spectrum of flow conditions.

Inter-method differences (SIMS vs. IRMS) in oxygen isotope fractionation: insights from Chinook salmon otoliths - Kohma Arai; Malte Willmes; George E. Whitman; Kenneth W. Zillig; Cassidy J. Cooper; Nozomi Matsuda; Elizabeth A. Bell; Kevin D. McKeegan; Levi S. Lewis; Carson A. Jeffres; Rachel C. Johnson (Geochimica et Cosmochimica Acta, 2025)

Effects of doxycycline on prepatent and patent infections of Brugia pahangi in dogs and observations on the growth and survival of L3 in jirds and dogs - John W. McCall; Laura Kramer; Claudio Genchi; Jorge Guerrero; Michael T. Dzimianski; Abdelmoneim Mansour; Scott McCall; Ben Carson; Christopher C. Evans (Veterinary Parasitology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

FIMserv v.1.0: A tool for streamlining Flood Inundation Mapping (FIM) using the United States operational hydrological forecasting framework - Anupal Baruah; Supath Dhital; Sagy Cohen; Thanh Nhan Duc Tran; Hesham Elhaddad; C. Lyn Watts; Dipsikha Devi; Yixian Chen; Carson Pruitt (Environmental Modelling & Software, 2025)

Cyclodextrin-based liquid crystals: A novel approach to promote the formation of thermotropic cubic mesophases and their potential applications as electrolytes - Austin Che; Carson O. Zellmann-Parrotta; Diganta Sarkar; Jayar Espejo; Vladimir K. Michaelis; Todd C. Sutherland; Vance E. Williams; Chang-Chun Ling (Carbohydrate Polymers, 2025)

Functional brain network correlates of cardiorespiratory fitness and moderation by depression symptoms - Lauren R. Borrell; Andrew C. Venezia; J. Carson Smith (Brain Structure and Function, 2025)
Cardiorespiratory fitness may protect against or alleviate depression through neuroplastic mechanisms within disrupted brain networks underlying cognitive and affective symptoms. There is a scarcity of research examining the effects of cardiorespiratory fitness on functional brain networks in representative samples spanning adulthood. Further, little is known about the interaction of cardiorespiratory fitness with depression in these networks. To address this problem, this study made use of the NKI-Rockland sample dataset and magnetic resonance imaging to examine whether functional brain network features associated with cardiorespiratory fitness were moderated by depression symptom severity in a community sample of 217 participants (134 females, 83 males) between the ages of 18 and 71 ( M = 43.8 years, SD = 16.2). Cardiorespiratory fitness was positively associated with whole-brain modularity, between-network connectivity of the central executive and salience networks, and within-network connectivity of the default mode, central executive, and salience networks. The association of cardiorespiratory fitness and default mode network connectivity was stronger in the presence of moderate-to-severe depression symptoms. Taken together, these observations lend support to prior work that has demonstrated the associations of cardiorespiratory fitness with reduced concurrent and prospective depression risk and symptom severity. Depression symptoms moderated default mode network connectivity, suggesting that cardiorespiratory fitness may differentially impact neural substrates for those with moderate-to-severe depression symptoms.

Genomics and serotyping of Tenacibaculum maritimum outbreak isolates from Australia and New Zealand for guided vaccine development and stewardship - O. Rudenko; C. Angelucci; K. Kumanan; L. Delisle; J. Carson; R.N. Morrison; K.S. Hutson; A.C. Barnes (Aquaculture, 2025)

Diet Driven Differences in Host Tolerance Are Linked to Shifts in Global Gene Expression in a Common Avian Host‐Pathogen System - Erin L. Sauer; Carson Stacy; Weston Perrine; Ashley C. Love; Jeffrey A. Lewis; Sarah E. DuRant (Molecular Ecology, 2025)
Wildlife have become increasingly dependent on anthropogenic resources, altering interactions between individuals and subsequently disease transmission. Further, nutritional quantity and quality impact an individual's ability to mitigate damage caused by infectious disease. Thus, understanding how diet affects immune function is critical for predicting disease severity and transmission. Here, we use transcriptomics to explore the previously unstudied molecular mechanisms underpinning diet‐driven differences in pathogen tolerance. Using a widespread avian bacterial pathogen, we find significant diet‐driven differences in the expression of many genes encoding immune response and translational machinery proteins. Prior to infection, protein‐fed birds are more transcriptionally primed for infection than lipid‐fed birds, resulting in greater tolerance for protein‐fed birds during the recovery period. Given the importance of human supplemented food in wildlife disease systems, the molecular mechanisms by which interactions between diet and infection emerge provide insight into the ecological and immunological consequences of human behaviour on wildlife disease.

A global survey for dust devil vortices on mars using MRO context camera images enabled by neural networks - Susan J. Conway; Valentin T. Bickel; Lori K. Fenton; Manish R. Patel; Helen C. Carson; Antoine Blouin; Justin Crevier; Evan Blanc; Bao Nhi Nguyen; James A. Holmes; Brian Jackson; Lonneke Roelofs (Planetary and Space Science, 2025)

Springtime upwelling conditions influence microbial communities and dissolved thiamin compounds in the California Current Ecosystem - Kelly C. Shannon; Gillian St. John; Robin Gould; Christopher Hartzell; Hailey Matthews; Elizabeth J. Brennan; Luis M. Bolaños; Steven T. Lindley; John C. Field; Nate Mantua; Rachel Johnson; Carson Jeffres; et al. (Limnology and Oceanography, 2025)
Understanding dissolved concentrations of the essential coenzyme thiamin (vitamin B 1 ) can provide insights into the biological controls on highly productive upwelling systems such as the California Current Ecosystem. To connect thiamin availability with microbial communities in the California Current Ecosystem, we measured concentrations of dissolved thiamin and its biochemically related moieties (thiamin congeners) and 16S rRNA gene‐based microbial communities during the spring. We found that strong upwelling caused a depletion of dissolved thiamin precursor compounds and abiotic degradation products relative to periods of weak upwelling. Specific microbial taxa, including species of SAR11 ecotypes, Candidatus Nitrosopumilus, and SUP05 cluster, were also significantly enriched with strong upwelling. Our data provide evidence that alterations to microbial communities in the mixed layer that occur as a result of upwelling could constrain the availability of dissolved thiamin and its chemical congeners in the California Current Ecosystem.

Dynamics of hydrogen–ammonia–natural gas lean-premixed high-pressure flames - Tristan T. Shahin; Alexander J. Hodge; Benjamin K. Murdock; Thomas N. McLean; Keaton C. Koenig; Rohan M. Gejji; Robert P. Lucht; Carson D. Slabaugh (Fuel, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Electronic cigarettes alter cardiac rhythm and heart rate variability hyperacutely in mice - Jocelyn A. Castellanos; Carson G. Cornett; David H. Gonzalez; Liqiao Li; Karla Luna; Holly R. Middlekauff; Rajat Gupta; Maria C. Jordan; Dennis Rünger; Yifang Zhu; Xuesi M. Shao; Kenneth P. Roos; et al. (Toxicology and Applied Pharmacology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Bayesian statistical analysis reveals spatial heterogeneity in Cyclone Thane deposits from Southeast India - C. Gouramanis; A. Karthik; S. Srinivasalu; S. Carson; A.D. Switzer (Marine Geology, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Native tree species prosper while exotics falter during gap-phase regeneration, but only where deer densities are near historical levels - Anthony C. Yacucci; Walter P. Carson; Jenna C. Martineau; Curtis D. Burns; Brian P. Riley; Alejandro A. Royo; Thomas P. Diggins; Ian J. Renne (New Forests, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Serological and molecular typing of Tenacibaculum maritimum from New Zealand farmed salmon, Oncorhynchus tshawytscha - Karthiga Kumanan; Lizenn Delisle; Connie Angelucci; Ryan B.J. Hunter; Oleksandra Rudenko; Jeremy Carson; Richard N. Morrison; Andrew C. Barnes; Kate S. Hutson (Aquaculture, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

First record of plastic ingestion by a freshwater stingray - Paulo A.A. Trindade; Lúcio D.M. Brabo; Ryan Andrades; Valter M. Azevedo-Santos; Marcelo C. Andrade; Laura Candore; Serena B. Cabigliera; David Chelazzi; Alessandra Cincinelli; Carson A. Jeffres; Tommaso Giarrizzo (Science of The Total Environment, 2023)

Acardius acephalus in an aborted lamb - A. Morey Matamalas; F. Ridout; J. Dubuc; C. Bianco; R. Reichel; A. Carson (Journal of Comparative Pathology, 2023)

The case for stand management guidelines as dynamic as global change: Aspen forest stockings of the western Great Lakes - Michael T. Carson; John M. Zobel; Dustin R. Bronson; Amanda M. McGraw; Christopher W. Woodall; Christel C. Kern (Forest Ecology and Management, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Obesity as a premature aging phenotype — implications for sarcopenic obesity - Emily Nunan; Carson L. Wright; Oluwayemisi A. Semola; Madhan Subramanian; Priya Balasubramanian; Pamela C. Lovern; Ibra S. Fancher; Joshua T. Butcher (GeroScience, 2022)
Obesity and aging have both seen dramatic increases in prevalence throughout society. This review seeks to highlight common pathologies that present with obesity, along with the underlying risk factors, that have remarkable similarity to what is observed in the aged. These include skeletal muscle dysfunction (loss of quantity and quality), significant increases in adiposity, systemic alterations to autonomic dysfunction, reduction in nitric oxide bioavailability, increases in oxidant stress and inflammation, dysregulation of glucose homeostasis, and mitochondrial dysfunction. This review is organized by the aforementioned indices and succinctly highlights literature that demonstrates similarities between the aged and obese phenotypes in both human and animal models. As aging is an inevitability and obesity prevalence is unlikely to significantly decrease in the near future, these two phenotypes will ultimately combine as a multidimensional syndrome (a pathology termed sarcopenic obesity). Whether the pre-mature aging indices accompanying obesity are additive or synergistic upon entering aging is not yet well defined, but the goal of this review is to illustrate the potential consequences of a double aged phenotype in sarcopenic obesity. Clinically, the modifiable risk factors could be targeted specifically in obesity to allow for increased health span in the aged and sarcopenic obese populations.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Natural Intertidal Oyster Reef Growth Across Two Landscape Settings and Tidal Ranges - Molly C. Bost; Antonio B. Rodriguez; Justin T. Ridge; Carson B. Miller; Stephen R. Fegley (Estuaries and Coasts, 2021)

Immature Male Chimpanzees’ (Pan troglodytes schweinfurthii) Social Relationships with Adult Males, but Not Peers, Persist into Adulthood - Joel Bray; Carson M. Murray; Ian C. Gilby; Margaret A. Stanton (International Journal of Primatology, 2021)

Correction to: Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

The rate of dasotraline brain entry is slow following intravenous administration - Robert Lew; Cristian C. Constantinescu; Daniel Holden; Richard E. Carson; Vincent Carroll; Gerald Galluppi; Kenneth S. Koblan; Seth C. Hopkins (Psychopharmacology, 2020)
Rationale Drugs that rapidly increase dopamine levels have an increased risk of abuse. Dasotraline (DAS) is a dopamine and norepinephrine reuptake inhibitor characterized by slow oral absorption with low potential for abuse. However, it remains unclear whether intravenous (i.v.) administration would facilitate the rapid elevation of dopamine levels associated with stimulant drugs. Objective To assess the kinetics of DAS across the blood-brain barrier and time to onset of dopamine transporters (DAT) inhibition. Methods We compared the onset of DAT occupancy and the associated elevation of synaptic dopamine levels in rhesus monkey following i.v. administration of DAS or methylphenidate (MPH) using positron emission tomography (PET). Brain entry times were estimated by reductions in [ 18 F]-FE-PE2I binding to DAT in rhesus monkeys. Elevations of synaptic dopamine were estimated by reductions in [ 11 C]-Raclopride binding to D 2 receptors. Results Intravenous administration of DAS (0.1 and 0.2 mg/kg) resulted in striatal DAT occupancies of 54% and 68%, respectively; i.v. administered MPH (0.1 and 0.5 mg/kg) achieved occupancies of 69% and 88% respectively. Brain entry times of DAS (22 and 15 min, respectively) were longer than for MPH (3 and 2 min). Elevations in synaptic dopamine were similar for both DAS and MPH however the time for half-maximal displacement by MPH ( t = 23 min) was 4-fold more rapid than for DAS ( t = 88 min). Conclusions These results demonstrate that the pharmacodynamics effects of DAS on DAT occupancy and synaptic dopamine levels are more gradual in onset than those of MPH even with i.v. administration that is favored by recreational drug abusers.

The microbiota influences the Drosophila melanogaster life history strategy - Amber W. Walters; Rachel C. Hughes; Tanner B. Call; Carson J. Walker; Hailey Wilcox; Samara C. Petersen; Seth M. Rudman; Peter D. Newell; Angela E. Douglas; Paul S. Schmidt; John M. Chaston (Molecular Ecology, 2020)
Organisms are locally adapted when members of a population have a fitness advantage in one location relative to conspecifics in other geographies. For example, across latitudinal gradients, some organisms may trade off between traits that maximize fitness components in one, but not both, of somatic maintenance or reproductive output. Latitudinal gradients in life history strategies are traditionally attributed to environmental selection on an animal's genotype, without any consideration of the possible impact of associated microorganisms (“microbiota”) on life history traits. Here, we show in Drosophila melanogaster , a key model for studying local adaptation and life history strategy, that excluding the microbiota from definitions of local adaptation is a major shortfall. First, we reveal that an isogenic fly line reared with different bacteria varies the investment in early reproduction versus somatic maintenance. Next, we show that in wild fruit flies, the abundance of these same bacteria was correlated with the latitude and life history strategy of the flies, suggesting geographic specificity of the microbiota composition. Variation in microbiota composition of locally adapted D. melanogaster could be attributed to both the wild environment and host genetic selection. Finally, by eliminating or manipulating the microbiota of fly lines collected across a latitudinal gradient, we reveal that host genotype contributes to latitude‐specific life history traits independent of the microbiota and that variation in the microbiota can suppress or reverse the differences between locally adapted fly lines. Together, these findings establish the microbiota composition of a model animal as an essential consideration in local adaptation.

Novel life history tactic observed in fall‐run Chinook Salmon - Carson A. Jeffres; Christopher C. Adams (Ecology, 2019)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Erratum to: Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Andrew Leis; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Ranavirus could facilitate local extinction of rare amphibian species - Julia E. Earl; Jordan C. Chaney; William B. Sutton; Carson E. Lillard; Andrew J. Kouba; Cecilia Langhorne; Jessi Krebs; Rebecca P. Wilkes; Rachel D. Hill; Debra L. Miller; Matthew J. Gray (Oecologia, 2016)

Coastal sea level changes, observed and projected during the 20th and 21st century - M. Carson; A. Köhl; D. Stammer; A. B. A. Slangen; C. A. Katsman; R. S. W. van de Wal; J. Church; N. White (Climatic Change, 2016)

Development and application of molecular methods ( PCR ) for detection of Tasmanian Atlantic salmon reovirus - S C Zainathan; G Carlile; J Carson; K A McColl; M St. J Crane; L M Williams; J Hoad; N J G Moody; H M Aiken; G F Browning; B F Nowak (Journal of Fish Diseases, 2015)
Molecular ( PCR ) diagnostic tests for the detection and identification of aquareovirus in general, and Tasmanian Atlantic salmon reovirus ( TSRV ) specifically, were developed, and their diagnostic sensitivity and specificity were determined and compared with virus isolation in cell culture. Intralaboratory and interlaboratory comparison of PCR (conventional hemi‐nested RT‐PCR & RT ‐ qPCR ) and virus isolation in cell culture using finfish cell lines, CHSE ‐214 and EPC , was carried out for the detection and identification of TSRV using field samples of farmed Atlantic salmon Salmo salar, L. from various aquaculture sites around Tasmania. The interlaboratory comparison of diagnostic methods was carried out between two laboratories, AAHL ‐ CSIRO and DPIPWE ‐Tasmania. A total of 144 fish from nine sites (12–33 fish per site) were sampled from two regions of Tasmania (Tamar River estuary in the north and Huon River estuary in the south‐east) during late spring to early summer of 2009, and the data were analysed using different statistical approaches. The prevalence of TSRV ranged from 6% to 22% in both regions. All the diagnostic methods (data from both laboratories) had high specificity, while the estimated sensitivity varied between tests with RT ‐ qPCR being the most sensitive (95.2%) method followed by virus isolation and then conventional hemi‐nested RT‐PCR .

Combination paracetamol and ibuprofen for pain relief after oral surgery: a dose ranging study - Hartley C. Atkinson; John Currie; John Moodie; Simon Carson; Steven Evans; James P. Worthington; Leon J. Steenberg; Eileen Bisley; Chris Frampton (European Journal of Clinical Pharmacology, 2015)

Conditions for the validity of SNP-based heritability estimation - James J. Lee; Carson C. Chow (Human Genetics, 2014)

Relationship of diversity and habitat area in North Pacific plastic-associated rafting communities - Miriam C. Goldstein; Henry S. Carson; Marcus Eriksen (Marine Biology, 2014)

Projecting twenty-first century regional sea-level changes - A. B. A. Slangen; M. Carson; C. A. Katsman; R. S. W. van de Wal; A. Köhl; L. L. A. Vermeersen; D. Stammer (Climatic Change, 2014)

Microsatellite population genetics of the emerald ash borer (Agrilus planipennis Fairmaire): comparisons between Asian and North American populations - Carson C. Keever; Christal Nieman; Larissa Ramsay; Carol E. Ritland; Leah S. Bauer; D. Barry Lyons; Jenny S. Cory (Biological Invasions, 2013)

Ecosystem classifications based on summer and winter conditions - Margaret E. Andrew; Trisalyn A. Nelson; Michael A. Wulder; George W. Hobart; Nicholas C. Coops; Carson J. Q. Farmer (Environmental Monitoring and Assessment, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Laboratory evaluation of sample collection methods (organs vs swabs) for T asmanian salmon reovirus detection in farmed A tlantic salmon, S almo salar L . - S C Zainathan; J Carson; M St J Crane; B F Nowak (Journal of Fish Diseases, 2013)
The use of swabs relative to organs as a sample collection method for the detection of Tasmanian salmon reovirus ( TSRV ) in farmed T asmanian A tlantic salmon, S almo salar L., was evaluated by RT ‐q PCR . Evaluation of individual and pooled sample collection (organs vs swabs) was carried out to determine the sensitivity of the collection methods and the effect of pooling of samples for the detection of TSRV . Detection of TSRV in individual samples was as sensitive when organs were sampled compared to swabs, and in pooled samples, organs demonstrated a sensitivity of one 10‐fold dilution higher than sampling of pooled swabs. Storage of swabs at 4 °C for t = 24 h demonstrated results similar to those at t = 0. Advantages of using swabs as a preferred sample collection method for the detection of TSRV compared to organ samples are evident from these experimental trials.

The Victoria and Birrindudu Basins, Victoria River region, Northern Territory, Australia: a SHRIMP U–Pb detrital zircon and Sm–Nd study - C. J. Carson (Australian Journal of Earth Sciences, 2013)

Examination of behavioral strategies regulating cocaine intake in rats - Benjamin A. Zimmer; Carson V. Dobrin; David C. S. Roberts (Psychopharmacology, 2013)

Siderophore production by actinomycetes isolates from two soil sites in Western Australia - Joanna Lee; Armin Postmaster; Hooi Peng Soon; David Keast; Kerry C. Carson (BioMetals, 2012)

Divergence genetics analysis reveals historical population genetic processes leading to contrasting phylogeographic patterns in co‐distributed species - TAMARA M. McGOVERN; CARSON C. KEEVER; CHRISTOPHER A. SASKI; MICHAEL W. HART; PETER B. MARKO (Molecular Ecology, 2010)
Coalescent samplers are computational time machines for inferring the historical demographic genetic processes that have given rise to observable patterns of spatial genetic variation among contemporary populations. We have used traditional characterizations of population structure and coalescent‐based inferences about demographic processes to reconstruct the population histories of two co‐distributed marine species, the frilled dog whelk, Nucella lamellosa , and the bat star, Patiria miniata . Analyses of population structure were consistent with previous work in both species except that additional samples of N. lamellosa showed a larger regional genetic break on Vancouver Island (VI) rather than between the southern Alexander Archipelago as in P. miniata . Our understanding of the causes, rather than just the patterns, of spatial genetic variation was dramatically improved by coalescent analyses that emphasized variation in population divergence times. Overall, gene flow was greater in bat stars (planktonic development) than snails (benthic development) but spatially homogeneous within species. In both species, these large phylogeographic breaks corresponded to relatively ancient divergence times between populations rather than regionally restricted gene flow. Although only N. lamellosa shows a large break on VI, population separation times on VI are congruent between species, suggesting a similar response to late Pleistocene ice sheet expansion. The absence of a phylogeographic break in P. miniata on VI can be attributed to greater gene flow and larger effective population size in this species. Such insights put the relative significance of gene flow into a more comprehensive historical biogeographic context and have important implications for conservation and landscape genetic studies that emphasize the role of contemporary gene flow and connectivity in shaping patterns of population differentiation.

The ‘Expansion-Contraction’ model of Pleistocene biogeography: rocky shores suffer a sea change? - PETER B. MARKO; JESSICA M. HOFFMAN; SANDRA A. EMME; TAMARA M. MCGOVERN; CARSON C. KEEVER; L. NICOLE COX (Molecular Ecology, 2010)

Determination of the compositional change (1999–2006) in the pine forests of British Columbia due to mountain pine beetle infestation - Colin Robertson; Carson J. Q. Farmer; Trisalyn A. Nelson; Ian K. Mackenzie; Michael A. Wulder; Joanne C. White (Environmental Monitoring and Assessment, 2009)

Light reduction predicts widespread patterns of dominance between asters and goldenrods - Joshua A. Banta; Scott C. Stark; Martin H. H. Stevens; Thomas H. Pendergast; Anthony Baumert; Walter P. Carson (Plant Ecology, 2008)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

Spatiotemporal distribution of heparan sulfate epitopes during murine cartilage growth plate development - Ronald R. Gomes; Toin H. Kuppevelt; Mary C. Farach-Carson; Daniel D. Carson (Histochemistry and Cell Biology, 2006)

Intramuscular aripiprazole for the treatment of acute agitation in patients with schizophrenia or schizoaffective disorder: a double-blind, placebo-controlled comparison with intramuscular haloperidol - Raisa Andrezina; Richard C. Josiassen; Ronald N. Marcus; Dan A. Oren; George Manos; Elyse Stock; William H. Carson; Taro Iwamoto (Psychopharmacology, 2006)

Hypoxia increases VEGF-A production by prostate cancer and bone marrow stromal cells and initiates paracrine activation of bone marrow endothelial cells - Caroline Muir; Leland W. K. Chung; Daniel D. Carson; Mary C. Farach-Carson (Clinical & Experimental Metastasis, 2006)

A null model of exotic plant diversity tested with exotic and native species–area relationships - Scott C. Stark; Daniel E. Bunker; Walter P. Carson (Ecology Letters, 2006)
At large spatial scales, exotic and native plant diversity exhibit a strong positive relationship. This may occur because exotic and native species respond similarly to processes that influence diversity over large geographical areas. To test this hypothesis, we compared exotic and native species–area relationships within six North American ecoregions. We predicted and found that within ecoregions the ratio of exotic to native species richness remains constant with increasing area. Furthermore, we predicted that areas with more native species than predicted by the species–area relationship would have proportionally more exotics as well. We did find that these exotic and native deviations were highly correlated, but areas that were good (or bad) for native plants were even better (or worse) for exotics. Similar processes appear to influence exotic and native plant diversity but the degree of this influence may differ with site quality.

Effects of paroxetine on cardiovascular response to mental stress in subjects with a history of coronary artery disease and no psychiatric diagnoses - Michael Golding; Michael Kotlyar; Stanley W. Carson; Sherri Hoyler; Cindy Lazarus; Colin Davidson; Joseph Guzzo; Eric Sontz; J. C. Garbutt (Psychopharmacology, 2005)

Perlecan Knockdown in Metastatic Prostate Cancer Cells Reduces Heparin-binding Growth Factor Responses in vitro and Tumor Growth in vivo - Cristiana Savorè; Chu Zhang; Caroline Muir; Riting Liu; Jeffrey Wyrwa; Jun Shu; Haiyen E. Zhau; Leland W.K. Chung; Daniel D. Carson; Mary C. Farach-Carson (Clinical & Experimental Metastasis, 2005)

QTL associations for density and diameter in Pinus radiata and the potential for marker-aided selection - M. E. Devey; S. D. Carson; M. F. Nolan; A. C. Matheson; C. Te Riini; J. Hohepa (Theoretical and Applied Genetics, 2004)

Coral‐reef sounds enable nocturnal navigation by some reef‐fish larvae in some places and at some times - J. M. Leis; B. M. Carson‐Ewart; A. C. Hay; D. H. Cato (Journal of Fish Biology, 2003)
At Lizard Island, Great Barrier Reef, catches of fish larvae by light traps that broadcast nocturnal reef sounds (noisy traps) were compared with catches by quiet traps over two 2·5 week new‐moon periods in November (XI) 2000 and January (I) 2001. Three areas were sampled: near‐reef (NR, 500 m from the shore) in I, middle (M, 650 m) in I and XI and offshore (O, >1000 m) in XI. The most abundant taxa captured were Apogonidae, Blenniidae, Chaetodontidae, Lethrinidae, Mullidae and Pomacentridae. Significant differences in catch were found between areas, and a position effect was found at the O and M areas. At the NR and M areas, no taxa had significantly greater catches in quiet traps, but larvae of five taxa had significantly greater catches in noisy traps. These were (areas and times of greater catches): Apogonidae (NR; M XI), Mullidae (M I & XI), Pomacentridae (NR; M I & XI), Serranidae (M I) and Sphyraenidae (NR). At the offshore area, five taxa (Apogonidae, Blenniidae, Chaetodontidae, Mullidae and Pomacentridae) had significantly greater catches in quiet traps and only Lethrinidae had significantly greater catches in noisy traps. Thus some taxa (particularly apogonids and pomacentrids which had catches up to 155% greater in noisy traps, but also lethrinids and mullids, and perhaps others), were attracted to reef sounds at night, but this apparently varied with location and time. The sound‐enhanced catches imply a radius of attraction of the sound 1·02–1·6 times that of the light. More than 65 m from the speaker,the broadcast sound levels at frequencies typical of fish hearing were equivalent to background levels, providing a maximum radius of sound attraction in this experiment.

Role of peripheral afference during acquisition of a complex coordination task - R. G. Carson; C. J. Smethurst; M. Forner; D. P. Meichenbaum; D. C. Mackey (Experimental Brain Research, 2002)

A Spiking Neuron Model for Binocular Rivalry - Carlo R. Laing; Carson C. Chow (Journal of Computational Neuroscience, 2002)

Turning On and Off with Excitation: The Role of Spike-Timing Asynchrony and Synchrony in Sustained Neural Activity - Boris S. Gutkin; Carlo R. Laing; Carol. L. Colby; Carson C. Chow; G. Bard Ermentrout (Journal of Computational Neuroscience, 2001)

The water-soluble components of the essential oil of Melaleuca alternifolia (tea tree oil) suppress the production of superoxide by human monocytes, but not neutrophils, activated in vitro - C. Brand; A. Ferrante; R.H. Prager; T.V. Riley; C.F. Carson; J.J. Finlay-Jones; P.H. Hart (Inflammation Research, 2001)

Alleviation of aluminum toxicity to Rhizobium leguminosarum bv. viciae by the hydroxamate siderophore vicibactin - Nicola J. Rogers; Kerry C. Carson; Andrew R. Glenn; Michael J. Dilworth; Martin N. Hughes; Robert K. Poole (BioMetals, 2001)

Orthostatic intolerance and the postural tachycardia syndrome: genetic and environment pathophysiologies - David Robertson; John R. Shannon; Italo Biaggioni; Andrew C. Ertl; André Diedrich; Robert Carson; Raffaello Furlan; Giris Jacob; Jens Jordan; and Team (Pflügers Archiv - European Journal of Physiology, 2000)

Terpinen-4-ol, the main component of the essential oil of Melaleuca alternifolia (tea tree oil), suppresses inflammatory mediator production by activated human monocytes - P.H. Hart; C. Brand; C.F. Carson; T.V. Riley; R.H. Prager; J.J. Finlay-Jones (Inflammation Research, 2000)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Nocardiosis in tank‐reared Atlantic salmon, Salmo salar L. - M P. Bransden; J. Carson; B L. Munday; J H. Handlinger; C G. Carter; B F. Nowak (Journal of Fish Diseases, 2000)
Nocardiosis is an infection caused by aerobic Gram‐positive, branching, filamentous rods of the genus Nocardia . The organism is resident in both soil and plants ( Austin & Austin 1993 ; Frerichs 1993 ), and is closely related to Mycobacterium spp. Nocardiosis caused by Nocardia asteroides and N. seriolae (previously N. kampachi ) has been reported in several finfish species, both freshwater and marine. The first reported incidence was recorded by Valdez & Conroy (1963) in neon tetras, Hyphessobrycon innesi (Myers), and subsequently in other fish species, some of commercial significance including rainbow trout, Oncorhynchus mykiss (Walbaum) ( Snieszko, Bullock, Dunbar & Pettijohn 1964 ), brook trout, Salvelinus fontinalis (Mitchill), ( Campbell & MacKelvie 1968 ) and yellowtail, Seriola quinqueradiata (Temminck & Schlegel; Kubota, Kariya, Nakamura & Kira 1968 ). Despite two of these incidences occurring in salmonids, infection by Nocardia spp. in Atlantic salmon, Salmo salar L., has not previously been reported.

Genetic analysis of inbreeding depression in plus tree 850.55 of Pinus radiata D. Don. II. Genetics of viability genes - H. Kuang; T. E. Richardson; S. D. Carson; B. C. Bongarten (Theoretical and Applied Genetics, 1999)

Evidence for polynuclear iron(III) clusters in the root nodule bacterium, Rhizobium leguminosarum bv. viciae WSM710 - Timothy G. St. Pierre; Kerry C. Carson; John Webb; Andrew R. Glenn; Michael J. Dilworth (BioMetals, 1999)

Frequency Control in Synchronized Networks of Inhibitory Neurons - Carson C. Chow; John A. White; Jason Ritt; Nancy Kopell (Journal of Computational Neuroscience, 1998)

Review: Application of biotechnology to forestry – molecular biology of conifers - C. Walter; S.D. Carson; M.I. Menzies; T. Richardson; M. Carson (World Journal of Microbiology and Biotechnology, 1998)

Formation of 8-oxodeoxyguanosine in brain DNA of rats exposed to acrylonitrile - John Whysner; Robert E. Steward 3rd; Di Chen; Carson C. Conaway; Lynne K. Verna; John P. Richie Jr.; Nusrat Ali; Gary M. Williams (Archives of Toxicology, 1998)

An allele responsible for seedling death in Pinus radiata D. Don - H. Kuang; T. E. Richardson; S. D. Carson; B. C. Bongarten (Theoretical and Applied Genetics, 1998)

Synchronization and Oscillatory Dynamics in Heterogeneous, Mutually Inhibited Neurons - John A. White; Carson C. Chow; Jason Rit; Cristina Soto-Treviño; Nancy Kopell (Journal of Computational Neuroscience, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

IgG rheumatoid factors isolated by the surface-displaying phage library technique - Yi-Yuan Yang; Peter Fischer; Sy-Jye C. Leu; Tsaiwei Olee; Dennis A. Carson; P. P. Chen (Immunogenetics, 1997)

Specificity of siderophore-mediated transport of iron in rhizobia - K. C. Carson; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1994)

Specificity of siderophore-mediated transport of iron in rhizobia - K. C. Carson; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1994)

Siderophore and organic acid production in root nodule bacteria - K. C. Carson; S. Holliday; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1992)